Exercice1

Calculer les expressions suivantes :

a) pour x = 2/3

D= x + 2
E= 4 ( 1 - x )
F= x² - 4x + 1

Exercice 2

Réduire les expressions suivantes :

G= -3x + 5 - 7x + 2x - 6x - 6
I= 3 ( x - 5)
K= 3x + 5x (4 - 2x) - 2 (x² - 3x + 5 )
H= 4x + (5 - 8 x) - ( 3x - 4)
L = (4x - 1) (3x + 5) - (x - 7)

1

Réponses

2014-02-22T23:48:51+01:00
Bonsoir,

Exercice 1.

a) pour x = 2/3
D = x + 2 
   = 2/3 + 2
   = 2/3 + 6/3
   = 8/3
 
E = 4 ( 1 - x )
   = 4 (1 - 2/3)
   = 4 (3/3 - 2/3)
   = 4 * 1/3
   = 4/3
 

F = x² - 4x + 1
   = (2/3)² - 4*(2/3)  + 1
   = 4/9 - 8/3 + 1
   = 4/9 - 24/9 + 9/9
   = -11/9

Exercice 2 

G = -3x + 5 - 7x + 2x - 6x - 6
    = -14x - 1 

I =  3 ( x - 5)
  = 3x - 15

K = 3x + 5x (4 - 2x) - 2 (x² - 3x + 5 ) 
    = 3x + 20x - 10x² - 2x² + 6x - 10
    = -12x² + 29x - 10
  
 
H = 4x + (5 - 8 x) - ( 3x - 4) 
   = 4x + 5 - 8x - 3x + 4
   = -7x + 9
 
L = (4x - 1) (3x + 5) - (x - 7)
   = 12x² + 20x - 3x - 5 - x + 7
   = 12x² + 16x + 2